Investigating Generation Z’s perceptions of AI customer service representatives in organizations - Taiwo, Doyinsola Dorcas (My University, 2026)
The evolution of Artificial Intelligence (AI) is gradually transforming the dynamics of corporate communication, as many US organizations have integrated it into their strategies. However, despite AI's demonstrated value in organizations, concerns persist about customers' perceptions and experiences regarding AI’s ability to replicate human empathy, raising questions about its suitability as a customer service representative. The existing literature revealed that customers value AI for its speed and consistency, while others suggest that customers often perceive AI as impersonal or robotic, lacking empathy and contextual understanding. However, they often treat consumers as a homogeneous group, paying little attention to how specific age groups interpret and respond to these interactions. Thus, this study aims to fill the gap by exploring Gen Z's perceptions of AI customer service, given their digital inclinations, to provide richer insights into AI in communication. The study is grounded in two theoretical frameworks: the Technology Acceptance Model (TAM) by Davis (1989) and Computers Are Social Actors (CASA) by Reeves & Nass (1996), which will assess both the functional and social dimensions of how Gen Z perceives AI customer service representatives. TAM is applied to explain the usefulness, ease of use, attitude, and behavioral intention towards AI customer service. At the same time, CASA adds depth by exploring how Gen Z treats AI as social actors, responding to them with human-like expectations of trust and communication. This study employed an online survey of Gen Z from Kansas State University. TAM variables, including Perceived Usefulness and Ease of Use, influence attitudes and Behaviors, specifically measuring how cognitive factors shape perception. In contrast, CASA explains emotional factors and social presence, the relational concerns Gen Z has about AI. Preliminary findings suggest that functional perceptions, such as usefulness and social perceptions, including social presence, empathy, and cultural factors, collectively shape Generation Z’s responses to AI customer service representatives. These findings provide in-depth insights into the factors influencing the interaction between Gen Z and AI customer service representatives, as well as the implications of this interaction on organizational communication.
Keywords: Artificial Intelligence; Customer service; Technology acceptance; Computers are Social Actors